The Influence of Product Quality and Ticket Prices on the Purchasing Decisions of Whoosh High-Speed Train Users (Jakarta-Bandung) - Elizabeth; Kusumaningrum, Dewi (The Postgraduate School of Tourism Sahid Polytechnic, 2025)
Purpose: This study aims to determine whether product quality and ticket prices have a partial and simultaneous effect on the purchasing decisions of users of the Jakarta-Bandung Whoosh High-Speed Train Research Methods: The research method used is quantitative. Data collection with a questionnaire to 100 respondents who have used the Jakarta-Bandung Whoosh Fast Train The analytical method used is Multiple Linear Regression Analysis, T Test, and F Test. Results and discussion: The results of this study indicate that product quality and price partially and simultaneously have a positive and significant effect on purchasing decisions. Also, the determinant coefficient test shows that product quality and price have a contribution of 57.9% in influencing purchasing decisions. Meanwhile, the other 42.1% are other independent variables that are not included in this study. Implication: Based on this study, it is recommended that PT Kereta Cepat Indonesia China (KCIC) ensure that the quality of the products offered aligns with the set prices, or that prices reflect the quality value communicated.